Lacan Deleuze Badiou - Bartlett, A. J.; Clemens, Justin (Cambridge University Press, 2014)
The theoretical writings of Jacques Lacan, Gilles Deleuze and Alain Badiou stand at the heart of contemporary European thought. While the combined corpus of these three figures contains a significant number of references to each other's work, such references are often simply critical, obscure - or both. Lacan Deleuze Badiou guides us through these crucial, under-remarked interrelations, identifying the conceptual passages, connections and disjunctions that underlie the often superficial statements of critique, indifference or agreement. Working through the rubrics of the contemporary, time, the event and truth, Bartlett, Clemens and Roffe present a new, lucid account of where these three thinkers stand in relation to one another and why their nexus remains unsurpassed as a point of reference for contemporary thought itself. Key Features. The first book to examine Lacan, Deleuze and Badiou together Reconstructs a fundamental conceptual history of Badiou, Deleuze and Lacan's influences and intellectual context Identifies and examines the key themes in contemporary European thought: the event, time and truth Shows how Deleuze and Badiou have followed and contravened the Lacanian intervention without reverting to pre-Lacanian positions